2020
DOI: 10.1016/j.ejpn.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia and choreoathetosis presence and severity in relation to powered wheelchair mobility performance in children and youth with dyskinetic cerebral palsy

Abstract: Introduction: Power wheelchairs (PW) with head/foot steering systems are used as an alternative to joysticks in children with severe dyskinetic cerebral palsy (DCP). Mobility training programs are unstandardized to date, and insight on dystonia, choreoathetosis, and mobility performance may lead to greater independent mobility. Objective: To map the presence and severity of dystonia and choreoathetosis during PW mobility in DCP and their relation with mobility performance. Methods: Ten participants with DCP pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…27 In contrast, studies of power mobility report high performance even for children and adolescents in GMFCS levels IV to V with restricted hand function (Manual Ability Classification System levels IV-V). 27,28 With increasing evidence of the benefits of independent mobility and with sufficient mobility options available nowadays, it is time to close the gap between research and clinical practice. To encourage independent mobility from an early age and throughout life, therapists should provide available information to parents and those living with CP and make sure different mobility options are available in different settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In contrast, studies of power mobility report high performance even for children and adolescents in GMFCS levels IV to V with restricted hand function (Manual Ability Classification System levels IV-V). 27,28 With increasing evidence of the benefits of independent mobility and with sufficient mobility options available nowadays, it is time to close the gap between research and clinical practice. To encourage independent mobility from an early age and throughout life, therapists should provide available information to parents and those living with CP and make sure different mobility options are available in different settings.…”
Section: Discussionmentioning
confidence: 99%
“…A study of factors influencing wheeled mobility in children with CP showed that only a few achieve independent mobility in their manual wheelchairs even if they have good hand function and upper extremity range of movement 27 . In contrast, studies of power mobility report high performance even for children and adolescents in GMFCS levels IV to V with restricted hand function (Manual Ability Classification System levels IV–V) 27,28 . With increasing evidence of the benefits of independent mobility and with sufficient mobility options available nowadays, it is time to close the gap between research and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Such control interfaces have been developed in research environments [39,40], and manufactured and applied on an individual basis [24,27,41]. A clinical evaluation was done [42] with the Adremo head/foot steering system (Adremo Revalidatietechniek, The Netherlands).…”
Section: Support Of Head Positionmentioning
confidence: 99%
“…Although some (preliminary) results are available on the head support as control interface during wheelchair driving and the associated mobility performance [24,42], the performance and effectiveness of head support itself (i.e., the supporting function) during driving of the wheelchair has not yet been studied, and therefore deserves further attention.…”
Section: Dynamic Environmentsmentioning
confidence: 99%
“…Interventions in this group are mostly aimed at reducing dystonia and include invasive neuromodulation treatments such as intrathecal baclofen (Bonouvrie et al, 2019) and deep brain stimulation (Koy and Timmermann, 2017). In addition, advanced rehabilitation techniques (such as alternative computer access solutions and powered mobility (Bekteshi et al, 2020)) are commonly applied within this group. Frequent and effective monitoring of dystonia would be extremely important for the indication and evaluation of these interventions but is often not applied clinically due to time constraints and lack of objectiveness in quantifying severity.…”
Section: Introductionmentioning
confidence: 99%